If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 24 = 4 + -10 Reorder the terms: 24 + 3x = 4 + -10 Combine like terms: 4 + -10 = -6 24 + 3x = -6 Solving 24 + 3x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 3x = -6 + -24 Combine like terms: 24 + -24 = 0 0 + 3x = -6 + -24 3x = -6 + -24 Combine like terms: -6 + -24 = -30 3x = -30 Divide each side by '3'. x = -10 Simplifying x = -10
| 3(a+1)=5(a-1) | | x^3-2x^2-09+18=0 | | -112/16 | | 5x(3x-5)(x+1)=0 | | y=e^2x+17 | | Y=2x+a | | (9a-3)/3 | | Bj+m=j | | 16[x-3]=-80 | | 3d+2=12 | | X*.0147=(X-67) | | 11=3u-13 | | 11=3u+13 | | (x-67)=x*1.47 | | 6d+(5.5)=2d-(6.5) | | 6d+5.5=2d-(6.5) | | 6d+5.5=2d-6.5 | | 17x+3=17x | | -33*1/5 | | 288/6 | | (3/4)-(9/12) | | 68(x-3)=-2x+35.6 | | 10x+5y+15z= | | (x-1)(x+5)-(x+2)(x-3)=3(1+5x) | | -8x-18=6 | | (3/4)-(3/12)= | | y-21=2(x-9) | | m-8-2=4 | | TanX=27/32 | | 3/4-3/12 | | 5(3x-1)+7=2-(5x-3) | | F(x)=4x^2+7x-6 |